Chest compression fraction: A time dependent variable of survival in shockable out-of-hospital cardiac arrest. (December 2015) - Cheskes, Sheldon; Schmicker, Robert H.; Rea, Tom; Powell, Judy; Drennan, Ian R.; Kudenchuk, Peter; Vaillancourt, Christian; Conway, William; Stiell, Ian; Stub, Dion; Davis, Dan; Alexander, Noah; et al.
Abstract: Introduction: The role of chest compression fraction (CCF) in resuscitation of shockable out-of-hospital cardiac arrest (OHCA) is uncertain. We evaluated the relationship between CCF and clinical outcomes in a secondary analysis of the Resuscitation Outcomes Consortium PRIMED trial. Methods: We included patients presenting in a shockable rhythm who suffered OHCA prior to EMS arrival. Multivariable logistic regression was used to determine the relationship between CCF and survival to hospital discharge, return of spontaneous circulation (ROSC), and neurologically intact survival. We also performed a secondary analysis restricted to patients without ROSC in the first 10 min of EMS resuscitation. Results: Among the 2011 patients, median (IQR) age was 65 (54, 75) years, 78.2% were male, and mean (SD) CCF was 0.71 (0.14). Compared to the reference group (CCF < 0.60), the odds ratio (OR) for survival was 0.49 (95%CI: 0.36, 0.68) for CCF 0.60–0.79 and 0.30 (95%CI: 0.20, 0.44) for CCF ≥ 0.80. Results were similar for outcomes of ROSC and neurologically intact survival. Conversely, when restricted to the cohort who did not achieve ROSC during the first 10 min ( n = 1633), compared to the reference group (CCF < 0.60), the OR for survival was 0.79 (95%CI: 0.53, 1.18) for CCF 0.60–0.79 and OR 0.88 (95%CI: 0.56, 1.36) for CCF ≥ 0.80. Conclusions: In this study of OHCA patients presenting in a shockable rhythm, CCF was paradoxically associated with lower odds of survival. CCF is a complex measure and taken by itself may not be a consistent predictor of good clinical outcomes.